A Study of Attitudinal Disjuncts in English Versus Vietnamese - Lê Thị Khánh Chi (2011)
This is a qualitative and quantative study on the syntactic, semantic and pragmatic features of English and Vietnamese Attitudinal Disjuncts. We examined a great variety of linguistic devices functioning to mark ……